Mutual fund performance at long horizons - Bessembinder, Hendrik; Cooper, Michael J.; Zhang, Feng (Journal of Financial Economics, 2023)
The percentage of U.S. equity mutual funds that outperform the SPY ETF over the last 30 years decreases substantially as the horizon over which returns are measured is increased. Further, some funds with positive monthly alpha estimates have negative long-horizon abnormal returns. These results reflect positive skewness in the distribution of fund returns that increases with horizon, and highlight the limitations of conditional arithmetic means of short-horizon returns (e.g., alpha) for long-horizon investors. We tabulate an aggregate wealth loss of $1.02 trillion to mutual fund investors over our 30-year sample, when opportunity costs are based on beta-adjusted SPY returns.